Migration policies and regional cooperation in the Southern Cone: institutional management of the Venezuelan migration in Argentina, Chile and Bolivia - Gissi, Nicolás (2021)
The objective of the article is to analyze the exodus of people from Venezuela, the most relevant migratory and humanitarian crises in Latin America in the last five years. An analysis of the evolution of migration policies in Chile, Argentina and Bolivia is carried out, based on a legislative review, policy analysis and a study on the institutional measures adopted by each country. Although there is an emerging international political coordination, the various particularities in force in each are also marked. The existence of State policies focused on migration issues such as in Chile and Argentina, as well as the circumstantial reaction of cases such as Bolivia, have been a fundamental key in the exercise of efforts and international cooperation. Venezuelan migration has become a priority in South America, implementing particular policies that are not enough, requiring greater regional coordination and collaboration, which has become more complex since 2020 given the health crisis caused by the Covid epidemic-19, which generated the closure of national borders.